Sintesis dan Evaluasi Antimalaria In Vitro Turunan Kinin Terhadap Plasmodium falciparum - Salahuddin, Salahuddin; K, Rahmana Emran; Hanafi, Muhammad; Sundowo, Andini; NL, Puspa Dewi; Adipratiwi, Nadia; Ariyani, Titin; Prabandari, Erwahyuni Endang; Waluyo, Danang (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2021)
Nowadays kinin is the most effective antimalarial drug and its used as an alternative in malaria treatment. However, toxicity of quinine restrict its use as an antimalarial drug. Lipophilicity and long half-life (t½) of quinine that reach 10-20 hours are responsible for its toxicity. The aim of this research is to obtain more polar quinine derivatives by means of hydrogen peroxide reactions to reduce the toxicity. The reactions using hydrogen peroxyde is performed analogously to the procedures reported in the literature. Extract of pure anhydrous kinin is purified in coloumn chromatography followed by structure elucidation. Synthetic product is tested in vitro against Plasmodium falciparum. The characterization of reaction products is performed with proton (1H) and carbon 13 (13C) nuclear magnetic resonance (NMR) spectroscopy. It showed that the reaction using reagents led to epoxidation of vinyl substituents of chinuclidine ring with 61,08% yields. Antimalarial test against Plasmodium falciparum obtained 1.250-2.500 μg/mL of IC50 value. The IC50 values indicated that the synthesis products were not potential for malaria treatment.